Energy harvesting from wind by a piezoelectric harvester. (15th February 2017) - Tao, J.X.; Viet, N.V.; Carpinteri, A.; Wang, Q.
Highlights: A novel wind power harvester using piezoelectric effect is developed. An optimal and practical design of the efficient energy harvester is proposed. A mathematical model is developed to describe the energy harvesting process. A high electric power up to 150 W is harvested. Abstract: A novel wind power harvester using piezoelectric effect is developed. This engineering structure device employs a wind turbine that extracts kinetic energy from the wind and converts it into the rotational motion of a shaft. The rotational shaft is connected to a Scotch yoke mechanism that is used for converting the rotational motion into linear vibrations of two piezoelectricity-levers through springs. A mathematic model is developed to calculate the root mean square value of the generated electric power. The influences of some practical considerations, such as the rotational speed of the wind turbine and the stiffness of the springs, on the root mean square of the generated power are discussed. The research results show that a power up to 150 W can be harvested for a piezoelectric wind turbine with a radius of blades of 1 m at the wind speed of 7.2 m/s, and the designed angular velocity of 50 rad/s.